The Impact of Peripheral Artery Disease in Chronic Total Occlusion Percutaneous Coronary Intervention (Insights From PROGRESS-CTO Registry). (March 2020) - Xenogiannis, Iosif; Gkargkoulas, Fotis; Karmpaliotis, Dimitri; Alaswad, Khaldoon; Krestyaninov, Oleg; Khelimskii, Dmitrii; Choi, James W.; Jaffer, Farouc A.; Patel, Mitul; Mahmud, Ehtisham; Khatri, Jaikirshan J.; Kandzari, David E.; et al.
The impact of peripheral artery disease (PAD) in patients undergoing chronic total occlusion (CTO) percutaneous coronary intervention (PCI) has received limited study. We reviewed 3999 CTO PCIs performed in 3914 patients between 2012 and 2018 at 25 centers, 14% of whom had a history of PAD. We compared the clinical and angiographic characteristics and procedural outcomes of patients with versus without history of PAD. Patients with PAD were older (67 ± 9 vs 64 ± 10 years, P < .001) and had a higher prevalence of cardiovascular risk factors. They also had more complex lesions as illustrated by higher Japanese CTO score (2.7 ± 1.2 vs 2.4 ± 1.3, P < .001). In patients with PAD, the final crossing technique was less often antegrade wire escalation (40% vs 51%, P < .001) and more often the retrograde approach (23 vs 20%, P < .001) and antegrade dissection/reentry (20% vs 16%, P < .001). Technical success was similar between the 2 study groups (84% vs 87%, P = .127), but procedural success was lower for patients with PAD (81% vs 85%, P = .015). The incidence of in-hospital major adverse cardiac events was higher among patients with PAD (3% vs 2%, P = .046). In conclusion, patients with PAD undergoing CTO PCI have more comorbidities, more complex lesions, and lower procedural success.